Strategies of Rodent Control Methods at Airports (Global Journal of Science Frontier Research, 2014)
Rodent populations at airports can cause human safety issues by attracting raptors ... be, expended to reduce of rodent populations at an airport may decrease birds population in the area and therefore, reduce the risk that raptors pose to aircraft. Rodent populations can be reduced by population management (i.e., use of rodenticides) or by habitat management (i.e., vegetation management, barriers, and land uses) that reduces the area's carrying capacity for rodents. We discuss potential approaches to reduce rodent populations at airports within the context of an integrated pest management strategy.
Keywords: aircraft; habitat management; integrated pest; management strategy; raptors; rodent; rodenticides; vole; wildlife damage